Laughter and Subjective Health Among Community-Dwelling Older People in Japan: Cross-Sectional Analysis of the Japan Gerontological Evaluation Study Cohort Data. Issue 12 (December 2015) - Hayashi, Kei; Kawachi, Ichiro; Ohira, Tetsuya; Kondo, Katsunori; Shirai, Kokoro; Kondo, Naoki
Abstract : Abstract: The aim of this study was to evaluate the association of laughter with subjective health independent of socioeconomic status and social participation among older people in Japan. We used the data of 26, 368 individuals (men, 12, 174; women, 14, 194) 65 years or older who participated in the Japan Gerontological Evaluation Study (JAGES) in 2013. Participants provided information on laughter and self-rated health, depression, socioeconomic, and psychosocial factors. We evaluated laughter from three perspectives: frequency, opportunities, and interpersonal interactions. Even after adjustment for depression, sociodemographic factors, and social participation, the prevalence ratio for poor subjective health among women who never or almost never laugh was 1.78 (95% confidence interval, 1.48–2.15) compared with those who reported laughing every day. Similar associations were observed among men. Laughter may be an important factor for the promotion of general and mental health of older adults. The mechanisms linking laughter and health warrant further study.